The inflammatory cytokine interleukin-23 is elevated in lung cancer, particularly small cell type - Cam, Caner; Karagoz, Bulent; Muftuoglu, Tuba; Bigi, Oguz; Emirzeoglu, Levent; Celik, Serkan; Ozgun, Alpaslan; Tuncel, Tolga; Top, Cihan (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of the study: Interleukin (IL)-17 and IL-23 play roles in inflammation and autoimmunity. The function of the IL-17/IL-23 pathway has not been completely evaluated in cancer patients. We aimed to investigate serum IL-17 and IL-23 levels and their relationship with clinicopathological and biochemical parameters in lung cancer patients. Material and methods: Forty-five lung cancer patients and 46 healthy volunteers were included in the study. IL-17 and IL-23 measurements were made with the ELISA method. The ages of patients (53–84 years) and healthy subjects (42–82 years) were similar. Results : Serum IL-23 levels were higher in lung cancer patients than in healthy subjects (491.27 ±1263.38 pg/ml vs. 240.51 ±233.18 pg/ml; p = 0.032). IL-23 values were higher in small cell lung cancer (SCLC) patients than in non-small cell lung cancer (NSCLC) patients (1325.30 ±2478.06 pg/ml vs. 229.15 ±103.22 pg/ml; p = 0.043). Serum IL-17 levels were lower in the patients, but the difference was not statistically significant (135.94 ±52.36 pg/ml vs. 171.33 ±133.51 pg/ml; p = 0.124). Presence of comorbid disease (diabetes mellitus, hypertension or chronic obstructive lung disease) did not have any effect on the levels of IL-17 or IL-23. Erythrocyte sedimentation rate values were positively correlated with cytokine levels, but serum albumin levels were negatively correlated. Conclusions : Serum IL-23 levels are elevated in lung cancer patients, particularly those with SCLC. IL-17 and IL-23 values are correlated with inflammatory markers in the patients.